Fathers and Sons - McMillan, M. author. aut Link
XI, 211 p.
Keywords: This book traces the rise of the political dynasty in the Middle East and, in the process, provides the context for the current Arab uprising. The author shows that a father-to-son transfer of power has no basis in Islam, and yet the idea of dynastic power became entrenched in the Middle East.